Foliar versus soil phosphorus (P) application for improving P use efficiency in wheat and maize in calcareous soils. (7th May 2021) - , Rafiullah; Khan, Mohammad Jamal; Muhammad, Dost; Mussarat, Maria, Huma; Adnan, Muhammad; Fahad, Shah; Wahid, Fazli; Arif, Muhammad, Amanullah
Abstract: Phosphorus (P) is the most deficient nutrient in agricultural soils after nitrogen. Additionally, exogenously applied P quickly transforms into less soluble compounds through various chemo-sorption reactions resulting in poor fertilizer use efficiency (15–25%). Therefore, this pot experiment was conducted to investigate the impact of foliar P (0, 45, 90 and 135 mM KH2 PO4 ) in conjunction with soil applied P (0, 10 and 20 mg P kg −1 ) for enhanced growth and P use efficiency of maize and wheat in calcareous soils. There was a linear increase in plant height and biomass both with the increasing application of soil and foliar P in both wheat and maize crop. However, the effect of foliar P was more pronounced in P deficient condition compared to 10 or 20 mg P kg −1 . Soil applied P at 10 and 20 mg P kg −1 increased plant dry biomass by 10.8 and 16.8% in maize and by 29.9 and 35.5% in wheat over control, respectively. Foliar P application didn't improve soil phosphorus. The interaction between soil and foliar P was significant ( p ≤ .05) showing that increase of either foliar or soil P application, tissue P content of both maize and wheat increased. In both season the higher foliar P solution resulted in higher P uptake though the increase in wheat were lower than maize. Therefore, the low recovery of soil P associated with poor soil characteristics could be corrected through its foliar application if administered at proper growth stage with suitable concentration strength and appropriate source.